An innovative decision-making scheme for the high-quality economy development driven by higher education - Ming Ji; Yiwen Jiao; Na Cheng (Journal of Innovation & Knowledge (JIK), 2023)
It is essential to adhere to innovative leadership and teach students in accordance with their aptitude through the sustainable development of higher education. Promoting high-quality development of local universities is demanded and needed for the adaptive talent in this new era. This work aims to explore how high-quality higher education can provide innovative decision-making solutions for economic development in the digital economy (DE) era. First, the role of higher education in economic development is analysed. Then, the importance of human capital cultivated by higher education to economic development is explained. The innovations are as follows. (1) A high-quality economic development index system in the Yangtze River Basin is established according to the requirements of quality change, dynamic change, and efficiency change in the economic development of the Yangtze River Economic Zone (YREZ). (2) The entropy weight method in intelligent decision-making and TOPSIS sorting technology are used to study the dynamic relationship between DE development and the premium-quality economic advance of the provinces and cities in the YREZ from 2015 to 2021. (3) The analysis part adopts three indicators of mean logarithmic deviation, Theil index, and the Gini coefficient to discuss the regional differences in economic development. Finally, a targeted development strategy is proposed. The results indicate that the DE level of each province in the YREZ in recent years has reached a maximum of 3.9309 and a minimum of 0.2844. The economic development of each province is relatively different, and the level of development is uneven. The overall Moran's I of the premium-quality economic development level of the YREZ in recent years is greater than 0, passing the significance test. This result suggests a positive spatial autocorrelation between them. The research provides data support for the formulation of economic development strategies for the YREZ in the future and reflects the key role of higher education in human capital training and economic development.
Keywords: 650; Digital economy; Economic advance strategy; Premium-quality economic advance; Tertiary education; YREZ